How Does the University Food Environment Impact Student Dietary Behaviors? A Systematic Review - Li, Xingbo; Braakhuis, Andrea; Li, Zengning; Roy, Rajshri (Frontiers in Nutrition, 2022)
The food environment has been implicated in creating an obesogenic generation; and while previous research has focused on population-wide initiatives, the university population resides in a research gap. To explore detailed components of the university food environment and what shaped dietary behaviors, we retrieved literature from the following databases: ScienceDirect, Scopus, PubMed, Medline, and EMBASE. Eleven studies were identified for qualitative content analysis and study quality assessment identified most of the studies as of good quality (n 8) and some as of fair quality (n 3). The certainty of evidence remained at a low level for all (n 11) studies due to the cross-sectional, observational nature of studies. Three major themes emerged: (1) food environment, (2) student perceptions (SPs), and (3) dietary outcome (DO). In a university food environment, the taste of food was paramount for the food choices of students, followed by the availability of food and the price of food. When university students perceive and choose foods and beverages, they sometimes regard unhealthy foods and beverages as healthy options. The diet quality of university students is more susceptible to living arrangements and socioeconomic status, but higher salt, fat, and added sugar consumption generally resulted in poorer quality of diet on campus. Future research could use novel methods to explore a wider range and deeper level of students' dietary behavior determinants in university food environments. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42021283562.